The Simultaneous Reduction of a Pair of Unitoid Matrices to Diagonal Form Revisited - Ikramov, Kh. D. (Computational mathematics and mathematical physics, 2024)
This note is an addendum to the paper on the same subject published by the author somewhat earlier. Its aim is to more precisely characterize pairs of unitoids that admit simultaneous reduction to diagonal form.